Scaling Up Thermal Retrofit of Residential and Public Buildings in Eastern Europe - World Bank Group (World Bank, Washington, DC, 2018)
The objective of this report is to identify policies, financing and delivery mechanisms with the view of scaling-up thermal retrofit of existing residential and public buildings in Bulgaria, Croatia, Poland, and Romania. These two segments of the building sector are critical to national goals for EE improvement, environmental protection and social development. Also, compared to other sectors, they remain underserved by existing programs and traditional financing mechanisms. With this in mind, the report focuses on Croatia and Bulgaria and identifies a menu of actionable and implementable interventions around program models, financing schemes, and institutional set-ups that take into account current policy and market conditions in the target countries, as well as examples of international good practice.